A Must-Know Guide to Complex Anal Fistulas: Supralevator, Extrasphincteric, and More - Sushila Muthaiya; Babu Peter Sathyanathan (Swiss Journal of Radiology and Nuclear Medicine, 2025)
Treatment of perianal fistulae, especially high-grade Grade 5 perianal fistula, is still a difficult procedure in colorectal surgery. Imaging is central to the correct classification, diagnosis, and preoperative evaluation of fistulae. The purpose of this article is to briefly present the five types of perianal fistula with Grade 5 complexity according to the radiological aspects, classification, and therapeutic implications.